2022
DOI: 10.3390/polym14194247
|View full text |Cite
|
Sign up to set email alerts
|

Durability against Wetting-Drying Cycles of Sustainable Biopolymer-Treated Soil

Abstract: The world today is more oriented towards sustainable and environmental-friendly solutions in every field of science, technology, and engineering. Therefore, novel sustainable and eco-friendly approaches for soil improvement have also emerged. One of the effective, promising, and green solutions is the utilization of biopolymers. However, even though the biopolymers proved to be effective in enhancing the soil-mechanical properties, it is still unknown how they behave under real environmental conditions, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 30 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…The results of this research are in line with the strengthening efficiency provided by (Qureshi et al, 2017) in which sand was collected from the Al‐Sharqia desert in Oman and mixed with XG biopolymer. The study performed by Soldo and Miletic (2022) on silty and clean sand using XG and GG and found that by mixing the biopolymer with sand, the strength was increased because of the adhesion between the biopolymer and the sand particles. Fatehi et al (2019) conducted a study using SA biopolymer in different percentages with dune sand and found that values increase as the biopolymer percentage increases, and the results were consistent with the present study.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this research are in line with the strengthening efficiency provided by (Qureshi et al, 2017) in which sand was collected from the Al‐Sharqia desert in Oman and mixed with XG biopolymer. The study performed by Soldo and Miletic (2022) on silty and clean sand using XG and GG and found that by mixing the biopolymer with sand, the strength was increased because of the adhesion between the biopolymer and the sand particles. Fatehi et al (2019) conducted a study using SA biopolymer in different percentages with dune sand and found that values increase as the biopolymer percentage increases, and the results were consistent with the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Carrageenan shows the strongest ability in strength loss prevention against water erosion. The durability of biopolymertreated soils has been examined by Soldo & Miletic (2022). They showed that the UCS of silica silty sand treated with Xanthan gum and Guar gum drops over 50% with one wet-dry cycle for 1% mass ratio of biopolymer.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, 0.5%, 1%, 1.5%, and 2% of the biopolymer by weight of the clay soil are mixed with the clay soil. In a plastic tray, the biopolymer powder and soil are thoroughly blended to guarantee that there are no biopolymer lumps [36,37]. Te geotechnical tests are conducted immediately after mixing the biopolymer into the soil.…”
Section: Sample Preparationmentioning
confidence: 99%